2015
DOI: 10.1148/radiol.14140500
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Normal Aorta Size in Children

Abstract: The range of normal effective diameters of the aorta at multiple levels and the common iliac arteries was determined for children of different sizes and both sexes. Measurements outside of the normal ranges are consistent with aneurysm or hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 13 publications
5
46
0
Order By: Relevance
“…The average aortic diameters found in this study are comparable to previous studies; men showed larger aortic dimensions than women . After normalizing ascending aorta diameter by BSA, no significant difference was observed between gender for the current cohort.…”
Section: Discussionsupporting
confidence: 88%
“…The average aortic diameters found in this study are comparable to previous studies; men showed larger aortic dimensions than women . After normalizing ascending aorta diameter by BSA, no significant difference was observed between gender for the current cohort.…”
Section: Discussionsupporting
confidence: 88%
“…There are multiple studies in adults evaluating normal values for aortic root measurements by CT, 7-9 but only 1 known in children. 2 Our results are similar to studies in the adult population, with echo consistently resulting in underestimation of the aortic root size. 9,10 Tsang et al 11 compared multiple levels of the aortic root by echo and contrast-enhanced, ECG-gated CT in a normal adult cohort and found that the echo measurements were significantly lower than CT measurements at all levels of the aortic root, confirmed by the slightly negative bias of transthoracic echocardiography.…”
Section: Discussionsupporting
confidence: 89%
“…Our cohort's aortic root measurements were similar to the reported aortic root measurements by contrast-enhanced MRI angiography and CT scan. 1,2 An average difference of 2.5 mm is clinically significant; 12.5% of our patients had an aortic root 5 mm bigger than the echo measurement indicated. We suspect that this underestimation is a result of the inability to align the probe precisely along the plane of the axis of the aortic root.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The detailed evaluation of vascular anatomy with multi‐detector row CT (MDCT) has reduced the need for interventional diagnostic procedures . The use of both modalities in children, however, is limited . The issue of radiation exposure is a concern in CT.…”
mentioning
confidence: 99%